God, The Mind's Desire: Reference, Reason and Christian Thinking (Modern theology, 2006)
Book reviewed: God, The Mind's Desire: Reference, Reason and Christian Thinking by Paul D. Janz (Cambridge: Cambridge University Press, 2004) xi + 232 pp. Reviewed by Michael Hanby Baylor University One Bear Place #97144 Waco, TX 76798-7144 USA